Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
PsycEXTRA Dataset 2000
DOI: 10.1037/e379712004-001
|View full text |Cite
|
Sign up to set email alerts
|

Youth With Mental Health Disorders: Issues and Emerging Responses

Abstract: This document is covered by a signed "Reproduction Release (Blanket) form (on file within the ERIC system), encompassing all or classes of documents from its source organization and, therefore, does not require a "Specific Document" Release form. This document is Federally-funded, or carries its own permission to reproduce, or is otherwise in the public domain and, therefore, may be reproduced by ERIC without a signed Reproduction Release form (either "Specific Document" or "Blanket").

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
188
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 31 publications
4
188
1
1
Order By: Relevance
“…C. A. Mallett (&) School of Social Work, Cleveland State University, 2121 Euclid Avenue, #CB324, Cleveland, OH 44115-2214, USA e-mail: c.a.mallett@csuohio.edu (Cocozza and Skowyra 2000). Most juvenile offenders meet criteria for at least one mental health disorder.…”
Section: Introductionmentioning
confidence: 99%
“…C. A. Mallett (&) School of Social Work, Cleveland State University, 2121 Euclid Avenue, #CB324, Cleveland, OH 44115-2214, USA e-mail: c.a.mallett@csuohio.edu (Cocozza and Skowyra 2000). Most juvenile offenders meet criteria for at least one mental health disorder.…”
Section: Introductionmentioning
confidence: 99%
“…However, the JJS has limited information to assess if and how often those needs are being met. Authors such as Hertz (2001) and Cocozza and Skowyra (2000) highlight the many obstacles present when the JJS attempts to address the mental health needs of youth in its care. One potential obstacle is the diminished likelihood that a youth will receive services when involved in two parallel systems (juvenile justice and mental health) unless a youth enters the mental health system via an alternative reason for entry (e.g.…”
Section: Evolution Of Guiding Principles the First Juvenile Court Wamentioning
confidence: 99%
“…Youth are then supervised by probation officers and case managers in conjunction with treatment providers. An evaluation of the PAIR program found that it provides an important service and coordinating function for youth, the courts, and the service systems involved (Cocozza and Skowyra, 2000). The National Mental Health Association (now called Mental Health America, or MHA) calls for effective treatment programs for juvenile offenders.…”
Section: Mental Health Screening Assessment and Treatmentmentioning
confidence: 99%
“…This program shares many components with the successful Linkages Project in Ohio (Cocozza and Skowyra, 2000). In that project, the Ohio county 1 The chi-square test used to measure statistical significance for this evaluation requires that each cell of a 2 × 2 table contain at least five observations.…”
Section: Mental Health Screening Assessment and Treatmentmentioning
confidence: 99%